Some Fixed Point Theorems Using Different Spaces in Banach Algebras (Journal of Informatics and Mathematical Sciences, 2025)
In this paper, it expands and generalize several fixed point theorems on multiple spaces and prove the existence and some operations of fixed points for nonlinear operators over Banach algebras. Results are extensions, proofs and generalizations of well-known findings from the literature. These findings represent Das et al. [7] generalized findings.